A study of the relationship between nurses' experience, structural empowerment, and attitudes toward computer use - Jehad A. Rababah; Mohammed M. Al-Hammouri; Wafa'a F. Ta'an (Elsevier, 2021)
Objective: This study examined the relationship between structural empowerment and nurses' experience and attitudes toward computer use. Methods: This study was conducted using a cross-sectional quantitative design. A total of 184 registered nurses from four hospitals in Jordan participated in the current study. Data were collected using a demographics questionnaire, the Conditions for Work Effectiveness Questionnaire-II (CWEQ-II), and the Pretest for Attitudes toward Computers in Healthcare (PATCH). Results: The median of experience in years among nurses was 5.0, ranging from one to 26 years. The mean score for the attitudes toward computer use was 61.90 ± 11.38. Almost half of the participants, 45.11%, were in the category of "feel comfortable using user-friendly computers." The participants' mean average of the total structural empowerment was 12.40 ± 2.43, and the values for its four subscales were: opportunity 3.57 ± 0.87, resources 2.83 ± 0.85, information 3.06 ± 0.79, and support 2.95 ± 0.86. The frequencies analysis revealed that most participants had a moderate level of empowerment (n = 127, 69.02%). The bivariate correlation between nurses' experience and attitudes toward computer use was significant (r = −0.17, P < 0.05). The relationship between the total structural empowerment score and attitudes toward computer use was positive but weak (r = 0.20, P < 0.01). Conclusion: The results indicated that more experienced nurses are more reluctant toward computer use. However, creating an empowering work environment can facilitate nurses' attitudes toward computer use.